Three-dimensional inter-basin groundwater flow toward a groundwater-fed stream: Identification, partition, and quantification - Han, Peng-Fei; Wang, Xu-Sheng; Zhou, Yangxiao; Yang, Zhi; Wan, Li; Chen, Jinsong; Jiang, Xiao-Wei (Journal of hydrology (Amsterdam), 2024)
•3D pathways of IGF are identified with an assessment on flow rates.•IGF contributes 36%∼59% to the baseflow and 32%∼52% to the streamflow in the studied river.•Infiltration recharge and aquifer properties affect the development of IGF. Inter-basin groundwater flow (IGF), defined as groundwater flows across the topographic divides, occurs in nature as a common phenomenon, and seriously affect water balance and solute transport in a basin. Although the existence of IGF has been checked in drainage basins with indirect methods, such as using information of hydrogeochemistry, few studies are conducted to directly identify and quantify the IGF in the three-dimensional (3D) space using numerical modeling of groundwater flow. In this study, we identify, partition and quantify IGF based on a regional-scale 3D groundwater flow model covering several traditional surface water basins. The investigation is focused on the Hailiutu River, a groundwater-fed stream in the Ordos Plateau, China. It is the first time that the source zones and 3D paths of IGF as well as its contribution to the streamflow are fully captured for a groundwater-fed stream. Results indicate that the IGF contributes 36%∼59% to the baseflow and 32%∼52% to the streamflow of the Hailiutu River, through different groups of circulation paths with the maximum depth up to ∼ 1000 m. Uncertainty analyses of the model show that the contribution of IGF to the streamflow is positively correlated to the infiltration recharge and hydraulic conductivities of the aquifer media. Several indirect methods are also checked for comparison, but they could only be used to assess the potential contribution of IGF, not the IGF paths. This study will facilitate in deeply understanding the evolution mechanism of the inter-basin groundwater circulation and the interaction between surface water and groundwater.